Effects of dietary phosphorus and calcium level on growth and skeletal development in rainbow trout (Oncorhynchus mykiss) fry - Fontagné, Stéphanie (2014)
The effects of dietary levels of phosphorus (P) and calcium(Ca) on skeletal development and mineral deposition in rainbow trout(Oncorhynchus mykiss) fry were studied. Six semi-purified diets were formulated with graded levels of P and Ca. The basal diet A contained only P supplied by casein at 0.5% of drymatter. Other diets B, C,D and Ewere supplementedwith 0.4, 0.8, 1.2 and 1.6% P supplied as a 1:1 mixture of NaH2PO4/KH2PO4 resulting in 0.8, 1.2, 1.6 and 2.2% total P, respectively. These five dietswere supplementedwith 1% Ca supplied as CaCO3whereas another diet F, supplementedwith 0.8% P,was Ca-free. Each dietwas distributed to 3 replicate tanks of 600 swimup fry (initialmean weight: 0.1 g) at a water temperature of 17 °C over a 12-week growth trial. Fish were handfed 6 times a day to visual satiety.